2021
DOI: 10.1038/s41467-020-20306-w
|View full text |Cite
|
Sign up to set email alerts
|

The order and logic of CD4 versus CD8 lineage choice and differentiation in mouse thymus

Abstract: CD4 and CD8 mark helper and cytotoxic T cell lineages, respectively, and serve as coreceptors for MHC-restricted TCR recognition. How coreceptor expression is matched with TCR specificity is central to understanding CD4/CD8 lineage choice, but visualising coreceptor gene activity in individual selection intermediates has been technically challenging. It therefore remains unclear whether the sequence of coreceptor gene expression in selection intermediates follows a stereotypic pattern, or is responsive to sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 47 publications
3
24
1
Order By: Relevance
“…A recent study added an analysis of chromatin accessibility to explore the subsequent development of the two lineages and computationally identify additional putative regulators (Chopp et al, 2020). While this study and another employing scRNA-seq (Karimi et al, 2021) led to important insights, the analyses did not provide sufficient temporal resolution to comprehensively pinpoint the early developmental stages (prior to the induction of THPOK and RUNX3). As a case in point, there is evidence for a late CD8-fated CD4+CD8+ thymocyte population (Saini et al, 2010), but this 4 population was not distinguished from earlier TCR signaled CD4+CD8+ populations that contain both CD4fated and CD8-fated cells (Chopp et al, 2020;Karimi et al, 2021).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study added an analysis of chromatin accessibility to explore the subsequent development of the two lineages and computationally identify additional putative regulators (Chopp et al, 2020). While this study and another employing scRNA-seq (Karimi et al, 2021) led to important insights, the analyses did not provide sufficient temporal resolution to comprehensively pinpoint the early developmental stages (prior to the induction of THPOK and RUNX3). As a case in point, there is evidence for a late CD8-fated CD4+CD8+ thymocyte population (Saini et al, 2010), but this 4 population was not distinguished from earlier TCR signaled CD4+CD8+ populations that contain both CD4fated and CD8-fated cells (Chopp et al, 2020;Karimi et al, 2021).…”
Section: Introductionmentioning
confidence: 95%
“…To this end, our data indicated that at subsequent stages (pseudotime 8-12), MHCI-specific thymocytes pass again through a DP phase on their way from the CD4+CD8low gate to the CD4-CD8+ gates, while the MHCII-specific lineage does not contain late-time DP cells. Although a population of later-time MHCI-specific DP cells has been previously described ("DP3"; Saini et al, 2010), it is not commonly accounted for (Park et al, 2020;Chopp et al, 2020, Karimi et al, 2021, resulting in a missing stage of CD8 T cell development and potential contamination of the DP gate with later-time CD8 lineage cells.…”
Section: Pseudotime Inference Captures Continuous Maturation Trajectory and Clarifies Intermediate Stages Of Developmentmentioning
confidence: 99%
“…ZBTB7B, also called THPOK (T-helper-inducing POZ/Kruppel-like factor), controls CD4 + vs. CD8 + T-cell lineage commitment in the thymus ( 74 ). Although not required for the β-selection and survival of thymocytes, ZBTB7B is selectively upregulated, likely by persistent TCR signaling that overrides the silencer activity of its distal regulatory element (DRE), in MHC-II-restricted CD69 + CD4 + CD8 low intermediate thymocytes (INTs) where lineage is thought to be determined ( 74 78 ). Functionally, disrupted expression/function of ZBTB7B redirects MHC-II-restricted INTs into the CD8 + lineage, while its overexpression converts MHC-I-restricted INTs into the CD4 + lineage ( Figure 1A ) ( 75 , 76 , 79 82 ).…”
Section: Zbtb Proteins Regulating Both the Development And Function Of T Cellsmentioning
confidence: 99%
“…Double-positive CD4 + CD8 + lymphocytes that receive a strong TCR-MHC-II signal, quickly stop the expression of CD8 and become single-positive CD4 + lymphocytes. In turn, CD4 + CD8 + lymphocytes that do not receive a relatively strong TCR-MHC-II signal for a long time stop the expression of CD4 + and become single-positive CD8 + lymphocytes (28). Thus, CD8 + lymphocytes undergo a stricter selection in the thymus.…”
Section: Introductionmentioning
confidence: 99%